(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Quinazolin-4(3H)-one derivatives are recognized as central nervous system (CNS) depressants. Epilepsy, the second most common neurological condition after headache, is characterized by recurrent seizures of cerebral origin. Fifty million people worldwide and an estimated 6 to 10 million people in India suffer from epilepsy. It is of concern that the diagnosis and management of epilepsy is often suboptimal in developing countries. There is a growing need for better, stronger, and safer therapeutic treatments for epilepsy. Quinazoline-4(3H)-ones were investigated as a potential next step in creating effective antiepileptic drugs. Herein, we report the synthesis of 3-(substituted benzylidine)-amino-2-phenylquinazolin-4(3H)-ones from 3-amino-2-phenylquinazolin-4(3H)-one under microwave irradiation as heating source wherever required. The compounds were evaluated for anticonvulsant potential using maximal electro-shock induced convulsions in mice. The chemical structures of the synthesized compounds were confirmed by fourier transform infra-red (FTIR), proton nuclear magnetic resonance (1H-NMR), and carbon-13 nuclear magnetic resonance (13C-NMR) studies. All the compounds were subjected to toxicity studies and then evaluated for their anticonvulsant activity against the maximal electroshock (MES) seizure method. LD50 was found to be 1098 mg/kg and the duration of tonic phase was reduced upto 1.1 sec and that of stupor phase was reduced upto 80 seconds. Most of the animals were protected from death after induction of convulsions. The structure-activity relationship of the compounds revealed that the 4(3H)-quinazolinone schiff bases; viz. 3-(N,N-dimethylamino-benzylidine)-amino-2-phenyl- quinazolin-4(3H)-one, 3-(p-chlorobenzylidine)-amino-2-phenyl-quinazolin-4(3H)-one and 3-(furan-2-yl methyleneamino)-2-phenylquinazolin-4(3H)-one; by significantly shortening the tonic and stupor phases of convulsions compared to controls, these compounds demonstrated strong anticonvulsant potential.